1995
DOI: 10.1021/ja00113a026
|View full text |Cite
|
Sign up to set email alerts
|

Slicing the Perovskite Structure into Layers: Synthesis of Novel Three-Dimensional and Layered Perovskite Oxides, ALaSrNb2MIIO9 (A = Na, Cs)

Abstract: NaLaSrNb2Co09 brown 3.967(5) NaLaSrNb2Ni09 gray 3.966(3) NaLaSrNb2Cu09 brown 3.978(5) NaLaSrNb2Zn09 white 3.988(4) CsLaSrNb2Cu09 gray 7.846(5) CsLaSrNb2Zn09 white 7.837 (8) 3-D perovskite 4.00 3-D perovskite 2.96 3-D perovskite 1.70 3-D perovskite 30.49(2) 2-D perovskite 1.68 30.66(3) 2-D perovskiteThe oxides possessing perovskite (CaTi03)-related structures are indeed legion.* 1 Besides the stoichiometric (ABO3) perovskites and their ordered variants (e.g., A2BB'06, AsBB^Oci), quite a few defective perovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…In accordance with the previous paper [7], CsLaSrNb 2 NiO 9 crystallized in a layered perovskite structure similar to that of CsCa 2 Nb 3 O 10 . The color of the prepared CsLaSrNb 2 NiO 9 powders is gray.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In accordance with the previous paper [7], CsLaSrNb 2 NiO 9 crystallized in a layered perovskite structure similar to that of CsCa 2 Nb 3 O 10 . The color of the prepared CsLaSrNb 2 NiO 9 powders is gray.…”
Section: Resultssupporting
confidence: 90%
“…As shown in figure 3, [9]. Different with NaLaSrNb 2 NiO 9 oxides that crystallizing in a 3-D perovskite, the CsLaSrNb 2-NiO 9 was crystallized in a 2-D layered perovskite structure because of the large tolerance factor [7]. It is reported that the layered perovskite CsLaSrNb 2 NiO 9 consists of perovskite-like slabs of composition [LaSrNb 2 NiO 9 ] interleaved by the large Cs cations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, from the scientific and technological point of view developing convenient and effective pathways for the synthesis of surfactant assisted nanostructures is of special significance. 21,22 It has been reported by Fujishima and Honda that the photocatalytic reaction has the potential to eliminate pollutants. Subsequently, extensive research efforts have been devoted towards environment and energy challenges.…”
Section: Introductionmentioning
confidence: 99%